1998
DOI: 10.1046/j.1523-1747.1998.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of BP180 (Type XVII Collagen) and α6 Integrin is Necessary for Stabilization of Hemidesmosome Structure

Abstract: The hemidesmosome is a multimolecular complex that integrates the extracellular matrix with the keratin cytoskeleton and that stabilizes epithelial attachment to connective tissue. A 180 kDa protein (BP180, type XVII collagen), first identified by its reactivity with autoantibodies in the serum of patients with a blistering skin disease called bullous pemphigoid (BP), is a transmembrane component of the hemidesmosome with a collagen-like extracellular domain. Here, using recombinantly expressed molecules and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
4
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 57 publications
0
49
4
2
Order By: Relevance
“…However, when these GABEB cells are induced to express BP180 protein, both BP180 and BP230 target to hemidesmosome-like structures at sites of cellsubstrate interaction, implying that there is a relationship between the two . In Hopkinson et al (1998), we showed that disruption of the association between BP180 and the ␣6␤4 integrin heterodimer does not result in a loss of colocalization of BP230 and BP180, suggesting the possibility that BP230 and BP180 are tightly coupled. In this work, we have provided the first direct evidence that BP180 and BP230 may interact and have shown that this interaction can be mediated by an association between the N-terminal cytoplasmic domain of BP180 and the N-terminal domain of BP230.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, when these GABEB cells are induced to express BP180 protein, both BP180 and BP230 target to hemidesmosome-like structures at sites of cellsubstrate interaction, implying that there is a relationship between the two . In Hopkinson et al (1998), we showed that disruption of the association between BP180 and the ␣6␤4 integrin heterodimer does not result in a loss of colocalization of BP230 and BP180, suggesting the possibility that BP230 and BP180 are tightly coupled. In this work, we have provided the first direct evidence that BP180 and BP230 may interact and have shown that this interaction can be mediated by an association between the N-terminal cytoplasmic domain of BP180 and the N-terminal domain of BP230.…”
Section: Discussionmentioning
confidence: 85%
“…The authors of two publications have speculated that BP180 and BP230 may form a complex at the site of the hemidesmosome Hopkinson et al, 1998). In the first of these studies, it was suggested that BP230 may interact with BP180 based on a study of immortalized keratinocytes derived from a patient with generalized atrophic benign epidermolysis bullosa (GABEB) in which BP180 was not expressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because laminin 332 is always present on the dermal side of 1-M NaCl-split skin 3,30 , the present data indicate that another binding molecule, or molecules, on the epidermal side is present in the ECM, which binds with the shed COL17 ectodomain more strongly than laminin 332 does. A candidate molecule is integrin α6, which is known to be able to bind with the ectodomain of COL17 31,32 . Alternatively, additional cleavage may occur in the C-terminus of COL17 when artificial blisters form by 1M NaCl.…”
Section: Discussionmentioning
confidence: 99%